Clinicopathological and molecular differences between stage IV screen-detected and interval colorectal cancers in the Flemish screening program - Neefs, Isabelle; Tran, Thuy Ngan; Ferrari, Allegra; Janssens, Sharon; Van Herck, Koen; Op de Beeck, Ken; Van Camp, Guy; Peeters, Marc; Fransen, Erik; Hoeck, Sarah; Van Hal, Guido (Frontiers in Oncology, 2024)
IntroductionInterval cancer (IC) is an important quality indicator in colorectal cancer (CRC) screening. Previously, we found that fecal immunochemical test (FIT) ICs are more common in women, older age, right-sided tumors, and advanced stage. Here, we extended our existing stage IV patient cohort with clinicopathological and molecular characteristics, to identify factors associated with FIT-IC.MethodsLogistic regression models were fit to identify variables associated with the odds of having a stage IV FIT-IC. Multivariate models were corrected for gender, age, and location.ResultsA total of 292 screen-detected (SD) CRCs and 215 FIT-IC CRCs were included. FIT-IC CRC had 5 fold higher odds to be a neuroendocrine (NET) tumor and 2.5 fold higher odds to have lymphovascular invasion. Interestingly, some variables lost significance upon accounting for location. Thus, tumor location is a critical covariate that should always be included when evaluating factors related to FIT-IC.ConclusionsWe identified NETs and lymphovascular invasion as factors associated with increased odds of having a stage IV FIT-IC. Moreover, we highlight the importance of tumor location as a covariate in evaluating FIT-IC related factors. More research across all stages is needed to clarify how these insights might help to optimize the Flemish CRC screening program.